Three species of Madagascan Plectronia transferred to Peponidium (Vanguerieae, Rubiaceae) - Davis, A. P.; Razafimandimbison, S. G. (Phytotaxa, 2014)
Three new combinations are made in the genus Peponidium: P. boivinianum, P. densiflorum and P. micranthum. A lectotype is designated for Plectronia boiviniana.